Grinchenkoʼs Pedagogical and Enlightening Activity: Historiography of the Research - Lashko, Myhaylo (Pedagogical Discourse, 2013)
In the article the historiographycal analysis of M.Grinchenkoʼs pedagogical and enlightening activity is made on the basis of chronological and problem-topical approaches. The main periods of her life and activity research are distinguished. The peculiarities of study of her life and activity by her contemporaries, Soviet and foreign scholars, emigrant and Ukrainian scholars in independent Ukraine are stated. It has been determined that her pedagogical and enlightening activity were studied fragmentarily and superficially without proper estimation of her role in the progress of Ukrainian pedagogical theory and school practice.